Right Coronary Artery STEMI following Blunt Thoracic Trauma - Saad Sikanderkhel; Jon-Austin Ash; Kimberly O’Dell; Jacob Mok; Harish Manyam; John Golding (Case Reports in Cardiology)
We present a case report of an otherwise healthy 37-year-old male without pertinent cardiac history or risk factors, who presented with cardiac trauma after a motor vehicle collision (MVC). Initial workup including electrocardiogram (ECG), transthoracic echocardiogram (TTE), and uptrending serial troponins warranted coronary angiography, during which occlusive thrombi were discovered in the proximal right coronary artery (pRCA), the right posterolateral vessel (rPL), and the right posterior descending artery (PDA). Subsequently, the patient underwent percutaneous coronary intervention of the RCA and PDA with aspiration thrombectomy. He was then initiated on dual antiplatelet therapy (DAPT) and recovered appropriately. This case is presented with the goal of enlightening the academic community of a rare complication while presenting a judicious approach to management in an attempt to decrease the occurrence of “near misses” in the future.